2012
DOI: 10.1166/jnn.2012.6359
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles Enhanced Luminescence of Terbium Complex in Solution for L-Dopa Determination

Abstract: Luminescent properties of a terbium (Tb3+)-L-3, 4-dihydroxyphenylalanine (L-dopa) complex by binding to colloidal silver nanoparticles (Ag NPs) have been presented. Luminescence intensity of the L-dopa complex was dramatically enhanced about 6-7 times by introducing Ag NPs. The Ag NPs concentration on the luminescent intensity was regarded as a main factor that balancing between an enhancing and a quenching effect of the Ag NPs. It was observed that changing the concentration of L-dopa causes the change in lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Recent studies found that some precious metal nanoparticles (e.g., silver (Ag), gold (Au)) can influence the fluorescence properties of RE complexes on account of the localized surface plasmon resonance (LSPR) effect of the precious metal nanoparticles [11][12][13][14][15][16]. LSPR arises from the resonant oscillation of conduction electrons on the surface of metal nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies found that some precious metal nanoparticles (e.g., silver (Ag), gold (Au)) can influence the fluorescence properties of RE complexes on account of the localized surface plasmon resonance (LSPR) effect of the precious metal nanoparticles [11][12][13][14][15][16]. LSPR arises from the resonant oscillation of conduction electrons on the surface of metal nanoparticles.…”
Section: Introductionmentioning
confidence: 99%